Characterization of Ti–6Al–4V Fabricated by Multilayer Laser Powder‐Based Directed Energy Deposition. Issue 6 (17th January 2022) - Ávila Calderón, Luis Alexander; Graf, Benjamin; Rehmer, Birgit; Petrat, Torsten; Skrotzki, Birgit; Rethmeier, Michael
Abstract : Laser powder‐based directed energy deposition (DED‐L) is increasingly being used in additive manufacturing (AM). As AM technology, DED‐L must consider specific challenges. It must achieve uniform volume growth over hundreds of layers and avoid heat buildup of the deposited material. Herein, Ti–6Al–4V is fabricated using an approach that addresses these challenges and is relevant in terms of transferability to DED–L applications in AM. The assessment of the obtained properties and the discussion of their relationship to the process conditions and resulting microstructure are presented. The quality of the manufacturing process is proven in terms of the reproducibility of properties between individual blanks and with respect to the building height. The characterization demonstrates that excellent mechanical properties are achieved at room temperature and at 400 °C. Abstract : Herein, multilayer laser powder‐based directed energy deposition (DED‐L) Ti–6Al–4V fabricated with a local protective gas atmosphere is characterized. The tensile properties at room temperature and 400 °C are proven excellent. The DED‐L additive build‐up is uniform and of high quality, as evidenced by homogeneous properties and microstructure between the individual blanks and with respect to the building height.